PENDAMPINGAN MANAJEMEN SANITASI MCK KOMUNAL, ECOPRINT, CROWDFUNDING, DAN TANGGAP BENCANA DI KELURAHAN PASIRKRATONKRAMAT - Auza'i, Mochammad Achsan; Zakiyya, Hariana Reksa; Rachmah, Anindya Ghaida; Humam, Arsy Alfan; Azaroh, Fika; Abdalla, M. Ulil Abshor; Fitriana, Dina; Riskiyani, Maulida; Yuliana, Novi; Faizah, Isyfinila; Salsabilla, Fanisa (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The condition of home toilets that are no longer functioning since the tidal flood and flood disasters has made communal toilets one of the sanitation solutions in Pasirkratonkramat Village, since sanitation is a very important need that must be met. Effective management of communal toilets can maximize the benefits that can be felt by the community. KKN 60 UIN Gusdur carries out assistance in the management of toilet management and procurement of administrative support equipment, a sign of appeal to maintain financial transparency and maintain the cleanliness of the toilets. Activities to advance children's creativity, Eco Print, are carried out at SDN Pasirsari 01 classes 4 and 5. The irony of the flood disaster occurred and inundated the former Pasirsari area, 511 residents took refuge in three evacuation posts. KKN 60 UIN Gusdur ensures that it opens crowdfunding for logistical package assistance that was successfully distributed to 60 non-evacuated families in three RTs and carries out information management and logistics management of flood disaster evacuation posts for one-way information management and distribution of evacuation logistics that are even and comprehensive.